African traditional leafy vegetables and the urban and periurban poor - Gockowski, J.; Mbazo'o, J.; Mbah, G.; Moulende, T. (Elsevier, 2003)
The importance of traditional leafy vegetables (TLVs) in nutrition and employment both in production and marketing among urban and peri-urban households was investigated. An expenditure model of demand using results from a 1998 survey (n=150) in Yaounde, Cameroon estimated that as a group TLVs were normal goods, which contribute a significant share of essential nutrients for the urban poor. Urban consumption of Brassica exotics, which have replaced TLVs in other parts of Africa, was minimal. Price analysis revealed a decline in supply during the dry season, which is a food security concern for the very poor. Field and market surveys conducted in 1998 and 1997 estimated that over 32000 households were engaged in producing and marketing TLVs under readily accessible entry conditions. Three production styles were identified: an intensive system within the urban limits, a semi intensive style in the urban periphery and an extensive style also in the urban periphery. The largest number of producers were women employing an extensive mixed crop system. Successful in situ conservation will require research to improve the productivity of TLV cropping systems and media efforts to promote their use.